A Case Report of Thoracic Ectopia Cordis in a Hospital in Zanjan, Iran - Mehdi Hosseini; Hassan Zamani; Shadi Moghimi; Aref Nekoufar (Case Reports in Pediatrics)
Background and Aim. Ectopia cordis is a rare congenital anomaly characterized by the heart being located partially or completely outside of the thoracic cavity. Thoracic ectopia cordis is an even rarer form of this anomaly, with only a few reported cases in the literature. The aim of this study was to present the clinical and radiological findings of a patient with thoracic ectopia cordis and discuss the management and outcomes of this rare anomaly. Methods. A 17-week-old female neonate with a history of prenatal diagnosis of congenital heart anomaly was admitted to Ayatollah Mousavi Hospital in Zanjan, Iran. For the diagnosis of thoracic ectopia, cordis fetal echocardiography and ultrasonography were performed. Moreover, the noninvasive prenatal testing (NIPT) genetic test performed in the 10th week of pregnancy was evaluated. Results. The neonate was diagnosed with thoracic ectopia cordis, with the heart located outside the thoracic cavity and covered by a thin membrane. The Z scores of the analyzed maternal venous blood chromosomes were between +6 and −6, and all chromosomes had a low risk in terms of the risk of birth defects. The results of this study revealed that genetic test analysis is not enough to diagnose and predict congenital anomalies and defects. Furthermore, the findings showed that the fetus’s mother continued to take folic acid after the first 3 months of pregnancy. This can be one of the risk factors involved in causing this heart defect. Conclusion. One of the important results of this study was that the diagnostic findings of ultrasound were normal, but the findings of echocardiography were reported as abnormal. This shows that fetal echocardiography is better than ultrasound imaging in diagnosing ectopia cordis. In addition, it is recommended that pregnant women should avoid taking folic acid after the first trimester of pregnancy.